Adverse Events of Bedaquiline Drug Use in the Treatment of Multidrug-Resistant Tuberculosis (MDR-TB) Patients: A Review Artcile - Nihlah, Nabilah A.; Almattin, Bilqis N.; Wicaksono, Imam A. (Universitas Padjadjaran, Indonesia, 2024)
Adverse Drug Reaction (ADR) is any unfavorable and unexpected drug response in patients dosed for prevention, diagnosis, or therapy. Tuberculosis is a contagious infectious disease caused by the bacterium Mycobacterium tuberculosis. Multi-drug resistance Tuberculosis (MDR TB) is caused by bacteria that are resistant to the two most powerful first-line anti-TB drugs - isoniazid and rifampicin; cases of resistance to both drugs result in worse treatment outcomes, longer treatment duration, high costs, and various other complications. All medications used to treat MDR TB patients have the potential to cause mild, moderate, and severe side effects, especially Bedaquiline. This article will explain information on drug side effects that occur in patients treated with MDR TB and Bedaquiline. The data was collected and discussed from primary journals through Google Scholar and PubMed online databases. Bedaquiline has the potential to cause side effects such as QT interval prolongation or irregular heart rhythm, cardiac arrhythmia, gastrointestinal disorders, joint and muscle pain, hearing loss, acne, and chest pain. Therefore, treatment of MDR TB with Bedaquiline requires monitoring to ensure patient compliance and early detection of possible side effects to ensure the safety and effectiveness of treatment.